2017
DOI: 10.1177/0266666917738042
|View full text |Cite
|
Sign up to set email alerts
|

Understanding social influence on mobile social networking sites: A social support perspective

Abstract: Due to the social networking relationship, users’ continuance of social networking sites (SNS) may receive social influence from their peers and referents. This research identified the effect of social support on social influence in mobile SNS. Social support consists of both informational support and emotional support. Social influence is reflected by three factors: subjective norm, social identity and group norm. The results suggested that social support has a significant effect on social influence. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 41 publications
1
13
0
3
Order By: Relevance
“…It is an important motivation for people to adopt new information technologies. Early research, for example, has shown that behaviors in adoption of e-mail (Fang, 1998), mobile phone services (Lee et al , 2009) and social networking sites (SNS) (Zhou, 2017) can all be influenced by social influence. With the rapid development of social commerce in recent years, the situation is similar in online shopping.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…It is an important motivation for people to adopt new information technologies. Early research, for example, has shown that behaviors in adoption of e-mail (Fang, 1998), mobile phone services (Lee et al , 2009) and social networking sites (SNS) (Zhou, 2017) can all be influenced by social influence. With the rapid development of social commerce in recent years, the situation is similar in online shopping.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Social media users with co-creation experience linked to practical problem-solving activities typically perceive greater social support than newcomers from the virtual community [ 71 ]. Because participants are socially influenced by their peers and referents, social (including informational and emotional) support from community members significantly affects subjective norms [ 72 ]. Experiences in online communities also positively affect social identity [ 73 ]—a predictor of external subjective norms [ 68 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In 2018, Cuppen [18] emphasized the value of social conflict in energy policy and planning and discussed several basic characteristics of social conflict. Zhou [19] proposed in 2019 that social support, including information support and emotional support, had a significant impact on social influence. Peng et al [20] presented an evaluation model to measure both direct and indirect influence based on the social relationship graph, by introducing friend entropy and interaction frequency entropy to describe the complexity and uncertainty of social influence.…”
Section: Literature Reviewmentioning
confidence: 99%